Quantifying the external and internal loads of professional rugby league training modes: consideration for concurrent field-based training prescription - Weaving, D.; Jones, B.; Till, K.; Marshall, P.; Earle, K.; Abt, G. (The Journal of Strength and Conditioning Research, 2020)
Practitioners prescribe numerous training modes to develop the varied physical qualities that professional rugby league players must express during competition. The aim of this study was to determine how the magnitude of external and internal training load per minute of time differs between modes in professional rugby league players. These data were collected from 17 players across 716 individual sessions (mean [SD] sessions: 42 [13] per player) which were categorized by mode (conditioning [CON], small-sided games, skills, and sprint training). Derived from global positioning systems (5 Hz with 15 Hz interpolation), the distances covered within arbitrary speed and metabolic power thresholds were determined to represent the external load. Session rating of perceived exertion and individualized training impulse represented the internal load. All data were made relative to the session duration. The differences in time-relative load methods between each mode were assessed using magnitude-based inferences. Small-sided games and CON very likely to almost certainly produced the greatest relative internal and external loads. Sprint training provided players with the greatest sprinting and maximal-power distances without a concomitant increase in the internal load. The metabolic power method complements speed-based quantification of the external load, particularly during small-sided games and skills training. In practice, establishing normative loads per minute of time for each mode can be useful to plan future training by multiplying this value by the planned session duration.